Shari’a Reservations in The Eyes of The Vienna Convention on The Law of Treaties - Bateel Naif Yamani (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2025)
The author tackles the concept of reservations under The Vienna Convention on The Law of Treaties of 1969, as an approach to achieve universality in the international legal sphere. The instrument in question can be an enabling tool that helps with development of international treaties, and motivates states globally to participate as active actors within the international system. Although many legal experts expressed their concern toward the usage of reservation, the contentious use of Shari’a reservations is faced with even a greater one. Although met with worries of hindering the effectiveness of international conventions, Shari’a reservations is seen as an imperative part of treaty development in the eyes of state sovereignty. The literature shows how reservations have been beneficial under Islamic law to Middle Eastern countries, serving Islamic states and enabling them to become active international actors.